2015
DOI: 10.1371/journal.pone.0117793
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Abscisic Acid Promotes Hypocotyl Growth and Affects Endoreduplication during Dark-Induced Growth in Tomato (Solanum lycopersicum L.)

Abstract: Dark-induced growth (skotomorphogenesis) is primarily characterized by rapid elongation of the hypocotyl. We have studied the role of abscisic acid (ABA) during the development of young tomato (Solanum lycopersicum L.) seedlings. We observed that ABA deficiency caused a reduction in hypocotyl growth at the level of cell elongation and that the growth in ABA-deficient plants could be improved by treatment with exogenous ABA, through which the plants show a concentration dependent response. In addition, ABA accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…Indeed, LeNCED1 transcripts accumulated significantly in the D-grown seedlings than in de-etiolated seedlings. 5 Altogether, our previously published results demonstrated ABA accumulation is required to stimulate the fast growth of tomato hypocotyl during skotomorphogenesis.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Indeed, LeNCED1 transcripts accumulated significantly in the D-grown seedlings than in de-etiolated seedlings. 5 Altogether, our previously published results demonstrated ABA accumulation is required to stimulate the fast growth of tomato hypocotyl during skotomorphogenesis.…”
mentioning
confidence: 70%
“… 11 Interestingly, there was marked great accumulation of free ABA in the elongating zone of hypocotyl, further supporting our published data. 5 Finally, the low concentration of free ABA in the root throughout the experimental period indicated that ABA probably has no or only a limited role during early root development in tomato seedling. However, a potential effect of artificial in vitro cultivation especially in root development cannot be excluded.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Although the level of ABA seems to play a key role in seed germination, a decrease in the endogenous ABA does not always correlate with germination [ 39 ] or is not sufficient to break dormancy in some dormant seeds [ 40 ]. Humplik et al [ 41 ] showed that ABA was essential for hypocotyl elongation and that appropriate control of the endogenous level of ABA was required in order to drive the growth of etiolated seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotyping system was equipped with a FluorCam unit for pulse amplitude-modulated measurement of chlorophyll fluorescence. After 20 min of dark adaptation, the standardized measurement protocol was applied, as described by Humplík et al (2015). The parameters F Po , F PSII , and F NPQ were calculated from the measured parameters according to Lazár (2015).…”
Section: Determination Of Gas-exchange Rates and Photosynthetic Parammentioning
confidence: 99%